INTRAVESICAL FOREIGN BODIES MIMICKING BLADDER CALCULI: A CASE REPORT - Amal, Rizki Jaya; Irfansyah; Putra, Aulia Rahman; Alvieda Nainggolan, Irbah Rea (Indonesian Journal of Urology, 2025)
Objective: In this case report, we will present a patient with an intravesical foreign body mimics bladder calculi. Case(s) presentation: A 37-year-old man presented with pain in the suprapubic area. The patient had a history of several urological procedures. First, at the age of 11 years, He had an augmentation cystoplasty due to a congenital neurogenic bladder. Later, at the age of 15 and 20, He experienced two traumatic bladder ruptures requiring open repair, and the Mitrofanoff appendicovesicostomy for intermittent self-catheterization was performed. Discussion: The patient underwent an emergency cystoscopy that revealed calcified cut ends of four urethral catheter tips. Cystolitholapaxy was performed to crush these calcified foreign bodies facilitating cystoscopic removal. Conclusion: A 37-year-old man presented with intermittent suprapubic pain caused by intravesical foreign bodies. Hence, Cystolitholapaxy was performed to remove these calcified foreign bodies. The patient was observed and discharged from the hospital after seven days of treatment. Keywords: Bladder, foreign bodies, suprapubic pain, vesica urinaria.